Práticas educativas e as inter-relações no ensino de história: metodologias ativas em sala de aula através da educação histórica - Difante, Francielle Alves (2023)
This master’s thesis refers to a research developed in the Graduate Program in Education at the Universidade Federal de Santa Maria (UFSM), whose objective is to carry out an analysis on the Teaching of History in basic education and the construction of memory and of historical consciousness during the teaching-learning process, linked to pedagogical practices interconnected with the use of Active Methodologies. Those methodologies are alternatives for the development of the teachinglearning process, with benefits and challenges for teachers. Thus, the objective is to understand how the teaching of History in basic education, specifically in the final years of Elementary School, has increased the need to problematize historical education, memory and historical consciousness through the enhancement of the curricular component and pedagogical practices associated with active methodologies. It is considered that educational practices linked to active methodologies favor the student's teaching-learning process since it is extremely important to connect the student to the classroom, and vice versa, but Brazilian education has been undergoing serious changes, the last being the implementation of the Base Nacional Curricular Comum (BNCC), where a denial of educational public policies is perceived, changing the format of emancipatory education. The central issue of this research is the question: How are Active Methodologies used in history teaching and how can they influence the construction of memory and historical consciousness within basic education? The research methodology has a character of theoretical and qualitative investigation, based on the current of Historical Education, through the use of a questionnaire to collect empirical data as a research instrument, thus analyzing the praxis of teachers and the application of Active Methodologies, their possibilities and weaknesses. In this way, this research, framed in the Line of Research “LP2: Educational public policies, educational practices and their interfaces“, of the PPGE/UFSM, allows a reflection on the process of construction of the Teaching of History and the methodologies used in the classroom that aim to build a conscious and critical student, contextualizing the contents developed with the school reality and its community. The analysis of the questionnaire made it possible to understand the interrelationship between practice in the classroom and the relationship between the school community and the environment in which it lives. The importance of the teaching-learning process, related to the teaching practice, enables the appreciation of the Teaching of History, approaching the reality of education in Brazil, in a way that makes sense for all the subjects involved, not just for the social layers that may still break with the dismantling of education and changes in public policies.